Trophic dynamics of a reservoir fishery following an introduction of a top predator: Insights from stable carbon and nitrogen isotopes. (2nd July 2020) - Wamboldt, James J.; Wanamaker, Alan D.; Carroll, Hannah M.; Schultz, Randall D.; Morris, Joseph E.
Abstract: Trophic dynamics and conceptual niche spaces of top piscivores were assessed using stable isotope analysis following the introduction of hybrid striped bass Morone saxatilis (Walbaum) × Morone chrysops (Rafinesque) into an established reservoir fishery devoid of gizzard shad, Dorosoma cepedianum (Lasueur). Hybrid striped bass were initially stocked into Three Mile Lake, Iowa as an attempt to biologically control pervasive yellow bass, Morone mississippiensis Jordan & Eigenmann, populations. From the analyses, it concluded that hybrid striped bass predominately targeted prey fish located in the littoral habitats of the reservoir and did not selectively consume yellow bass as intended. Bayesian isotope mixing models described the diets of hybrid striped bass to include a variety of prey fish, predominantly consisting of young bluegill Lepomis macrochirus and yellow bass. Food resource overlap among hybrid striped bass, largemouth bass, Micropterus salmoides Lacépède, and walleye, Sander vitreus (Mitchill), appeared substantial based on the isotopic niche overlap model. Results from this case study, in conjunction with the hindsight that yellow bass populations became prolific even with stockings of hybrid striped bass, suggest that their use to control yellow bass populations may not be a viable management strategy in southern Iowa.